A Cross-sectional Study on Hepatoprotective agents and Antimicrobials in Treatment of Liver Diseases - Haritha, Allu; shankar, Kakaraparthy Ravi; Susmitha, Kondepudi Sai; Reshma, Karapu; Chandramouli, Dwarapureddy; KM, Manokaran (Journal of Pharmacy Practice and Community Medicine)
Background: Liver diseases are one of the global health care problems with enormous social, economic, and clinical consequences accounting for death. Aim: our main aim is to promote the symptoms, complications of liver disease and to reduce the risk of disease, and evaluate the utilization and effectiveness of hepatoprotective agents along with the utilization of antimicrobials. Materials and Methods: This is a 6-month crosssectional study in a tertiary care teaching hospital with a sample size of 55 patients. The patient profile, questionnaire, and laboratory tests were used to gather information. Results: Among 55 patient’s alcoholic liver disease (36.36%) followed by chronic liver disease (34.54%), decompensated liver disease (12.72%), and liver abscess (16.36%) seen at a common age group of 40 –70 years in which males (87.27%) and females (12.72%) are affected. About 85.45% are habituated to be alcoholic and 14.54% are non-alcoholic. About 60% of patients experiencing ascites as a complication. Mostly prescribed drugs are antibiotics (80%) and hepatoprotective agents (78.18%) are cephalosporins and ursodeoxycholic acid respectively. This study showed a drop of 42% Serum bilirubin, 58% Aspartate transaminase, and 65% Alanine transaminase in patients having hepatoprotective agents in a time gap of 1 week. Conclusion: The study suggests that abstinence of alcohol along with the management of underlying symptoms with antibiotics and hepatoprotective agents may help in preventing further complications.
Keywords: Alcoholic liver disease; Decompensated liver disease; Chronic liver disease; Liver abscess; Hepatoprotective agents; Antibiotics.